Analisis Gaya Bahasa pada Syair “Kun Qawiyyan, Kun ‘Azizan” Karya Muhammad Awadh Muhammad (Studi Stilistika) - Syamsudin Ali, Al Walid; Rachmawati, Miatin (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
This study aims to identify the stylistic elements in the poem Kun Qawiyyan, Kun ‘Azizan by Muhammad Awad Muhammad, focusing on rhetorical devices such as rhetorical questions, antithesis, metaphor, and hyperbole. The research employs a qualitative approach through library research using printed and digital sources as the main corpus. The analysis is conducted descriptively and analytically based on Gorys Keraf’s theory of rhetorical style, encompassing the mapping of the poem’s structure and the interpretation of its meaning. The findings indicate that the poem’s expressive strength is closely related to the intellectual awakening of the modern Arab world in the early twentieth century. The rhetorical devices employed emphasize moral messages about rejecting weakness, upholding dignity, and cultivating a strong and independent character. These findings also relate to the intellectual background of the poet, a prominent Egyptian scholar with deep concern for literature and the socio-moral conditions of Arab society. The study concludes that the poem’s effectiveness lies in the integration of strong moral messages with stylistic strategies that enhance its expressive power. تهدف هذه الدراسة إلى الكشف عن العناصر الأسلوبية في شعر كن قويا، كن عزيزا لمحمد عوض محمد، مع التركيز على الأساليب البلاغية مثل الاستفهام البلاغي، والمقابلة، والاستعارة، والمبالغة. وتعتمد الدراسة المنهج النوعي من خلال البحث المكتبي باستخدام المصادر المطبوعة والرقمية بوصفها الرئيسية. وقد أُجري التحليل بطريقة وصفية تحليلية بالاستناد إلى نظرية الأسلوب البلاغي لغاريس كيراف، شاملا تحليل البنية الشعرية وتفسير الدلالات الكامنة فيها.وتُظهر النتائج أن القوة التعبيرية في هذه الشعر ترتبط ارتباطا وثيقا بحركة اليقظة الفكرية في العالم العربي الحديث مطلع القرن العشرين. إذ تُبرز الأساليب البلاغية المستخدمة رسائل أخلاقية تدعو إلى رفض الضعف، وصون الكرامة، وبناء شخصية قوية ومستقلة. وترتبط هذه النتائج كذلك بالخلفية الفكرية للشاعر، وهو عالم مصري بارز عُرف باهتمامه العميق بالأدب وبالأوضاع الاجتماعية والأخلاقية في المجتمع العربي. وتخلص الدراسة إلى أن فاعلية الشعر تكمن في الجمع بين رسائلها الأخلاقية القوية والاستراتيجيات الأسلوبية التي تُعزّز من قوّتها التعبيرية.